UPAYA PEMAHAMAN KONSEP MATEMATIKA MATERI PERKALIAN PADA SISWA SD DENGAN MENGGUNAKAN METODE HANDS ON ACTIVITY - Mariam, Lilis; Kelana, Jajang Bayu (IKIP Siliwangi, 2020)
The purpose of this study was to determine whether or not the hand on activity method affected the ability of elementary students to understand the mathematical concept of multiplication material. This study used a quasi-experimental method with a non-equivalent pretest-postest design. The population in this study were all class II SD Plus Al - Aitaam Bandung for the 2019/2020 academic year with a sample of 112 students. The sampling technique was taken by using a purposive sampling technique. In this study, two classes were used as the research sample and two classes were chosen to be used as research with the category A-class (II Utsman) as the experimental class and class B (II Hafsoh) as the control class. Based on the results of the ANOVA test, it turns out that in the learning class using the hands-on activity method with the lecture method the sig value = 0.040, and the value is smaller than α = 0.05, which means that H1 is accepted, H0 is rejected. Because Ha is accepted, the hypothesis which states that there are differences in the ability to understand mathematical concepts of students who learn to use hands-on activity with the lecture method is accepted. It can be concluded that there are differences in the ability to understand mathematical concepts of students who learn using the hands-on activity method with students who learn using the lecture method.